Knowledge on text neck syndrome among paramedical students - Kunnath, Anugraha Puthalan; Rameshan, Sankeerthana; Sudheendran, Deena Vachal; Rouff, Fathima; Chandran, Akash; Kkunnil, Sabna Pulikka (International Journal Of Community Medicine And Public Health, 2025)
Background: The smartphone has evolved into an essential tool for many individuals, serving both communication and entertainment purposes. However, the prevalence of " text neck syndrome" (TNS) is emerging as a significant health issue, potentially impacting a substantial portion of the global population. TNS is predominantly observed in adolescents, largely due to their prolonged use of handheld electronic devices. Current estimates suggest that approximately 75% of the global population spends several hours each day in a forward-leaning position while using these devices. Methods: A cross-sectional study to assess the knowledge on TNS was conducted with a sample size of 198 paramedical students from the Department of Bachelor of Physiotherapy at Thalassery, Kannur, Kerala. A convenience sampling method was employed, and informed consent was secured from each participant before data collection commenced. A structured survey questionnaire was developed, validated, and utilized in this research. Results: 59.5% of participants had poor knowledge, 25.5% had moderate knowledge, and 5% had good knowledge regarding TNS and also highlighted a significant association between knowledge and age, gender, year of study, educational status of parents, occupation of mother and duration of usage of hand-held electronic devices. Conclusions: The findings of this study highlight a significant lack of understanding regarding TNS among participants and 59.5% exhibiting insufficient knowledge. This lack of awareness is closely linked to factors such as age, gender, academic year, parental education, maternal occupation, and the amount of time spent using handheld electronic devices.